THE CONCEPT OF THE LYRICAL HERO AND THE POETIC REPRESENTATION OF FEMALE EXPERIENCE - M.A.Usmonova (International Journal of Literature and Language Studies, 2026)
This article explores the concept of the lyrical hero and its role in the poetic representation of female experience. The lyrical hero, as the artistic embodiment of the poet's emotions, thoughts, and worldview, serves as a crucial medium through which personal and collective female experiences are expressed in poetry. The study examines how female poets construct lyrical identities to articulate themes of selfhood, memory, motherhood, love, loss, social expectations, and the search for personal freedom. Particular attention is paid to the relationship between the author's voice and the lyrical hero, highlighting the ways in which poetic subjectivity contributes to the formation of a distinct female perspective. Drawing on literary and comparative analysis, the article investigates the artistic means employed to represent women's inner worlds, including imagery, symbolism, metaphor, and narrative voice. It argues that the lyrical hero functions not only as a poetic persona but also as a cultural and psychological construct reflecting the complexities of female consciousness and experience. Through the examination of selected poetic texts, the study demonstrates how poetry becomes a space for negotiating identity, challenging stereotypes, and articulating women's experiences across different social and cultural contexts. The findings reveal that the lyrical hero plays a significant role in shaping the artistic representation of female experience, allowing poets to transform personal emotions into universal poetic meanings. The research contributes to contemporary literary studies by expanding the understanding of gendered subjectivity and the poetic mechanisms through which women's voices are expressed and interpreted.